Best Answer

Gathering like terms together, this is equal to 5a + 3b + 7c.

Q: What is 3a plus 2b plus 3c plus 2a plus 4c plus b equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-2a plus 3b

2a + 3a + 4 = 5a + 4

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)

Related questions

1

a + a + a - 2a = 3a - 2a = a

-2a plus 3b

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).

= a + b - 2

2a + 3a + 4 = 5a + 4

1

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)